Relationship Between Emotional Maturity and Verbal Aggressiveness Among Students of SMKN 9 Muaro Jambi - Raditha Anaztasya; Akmal Sutja; Freddi Sarman (The Future of Education Journal, 2026)
This study was motivated by the emergence of verbal aggressiveness among students, such as yelling, mocking, insulting, and scolding in daily interactions. The purpose of this study was to determine the level of emotional maturity, the level of verbal aggressiveness, and the relationship between emotional maturity and verbal aggressiveness among students of SMKN 9 Muaro Jambi. This research used a quantitative approach with a correlational research design. The sample consisted of 183 students selected from SMKN 9 Muaro Jambi. Data were collected using Likert scale questionnaires and analyzed using descriptive statistics and Pearson Product Moment correlation analysis. The results showed that the level of students’ emotional maturity was in the moderate category with a percentage of 44.75%, while the level of verbal aggressiveness was also in the moderate category with a percentage of 50.03%. Furthermore, the correlation analysis revealed a significant relationship between emotional maturity and verbal aggressiveness with a correlation coefficient of -0.312, indicating a low negative correlation. This means that higher emotional maturity tends to be associated with lower verbal aggressiveness, whereas lower emotional maturity tends to increase verbal aggressiveness among students.